Structuralism, Empiricism, and Newman's Objection - Otávio Bueno; Thomas Meier (Principia: An International Journal of Epistemology)
Newman’s objection can be used to argue that structuralism fails to specify a unique structure for the unobservable world, and hence, one can argue, it is ultimately a trivial task to determine the structure that the world ultimately has. Provided there are enough objects, any structure can be made compatible with that structure. We formulate a pragmatically enriched version of structuralism that avoids the Newman objection. For this purpose, we return to Carnap’s conception of founded relations, and provide a different interpretation of them. According to Carnap, these are real, experienceable, physical relations. We argue that, when we specify a structural description of a given physical system, if we rely on such founded relations—provided they are properly understood—the threat of the Newman objection is avoided. However, pure structuralism has to be given up, and a form of empiricism can then be advanced. Finally, by using founded relations, we offer a framework in terms of which different conceptions (some realist, some empiricist) can be articulated to avoid the Newman problem as well.